P433 Intravenous ustekinumab as maintenance treatment is effective in patients with partial or loss of response to optimized ustekinumab sc. (21st January 2022) - Garcia-Alvarado, M; Barrio, J; Sierra-Ausin, M; Arias, L; Fernández-Salazar, L; Fuentes Coronel, A; Arias García, L; García-Alonso, F J; García-Prada, M; Legido, J; Sánchez-Hernández, J G; Muñoz, F
Abstract: Background: Ustekinumab is an effective drug in Crohn′s Disease (CD) and most frequently used dose is subcutaneous (sc), 90 mg /, 8 weeks. With the usual sc doses (90 mg every, 8–12 weeks) some patients will only partially respond or experience secondary loss of response. In this situation, shortening of the administration interval (e.g., every, 4 or, 6 weeks) or a reinduction dose has been proposed. Another unexplored option is intravenous (IV) administration at regular intervals when shortening sc dose is not effective enough. Methods: We conducted a retrospective study to evaluate the effectiveness of IV ustekinumab at regular intervals (usually every, 4–6 weeks) in patients with insufficient efficacy or loss of response to, 90 mg sc every, 4–6 weeks. All patients had active Ulcerative colitis (UC) or Crohn′s disease (CD) defined by partial Mayo score (pMS) or Harvey Bradshaw Index (HBI)>, 4 points and/or persistent biomarker elevation (calprotectin>, 250 µg/g) and/or endoscopic or radiological evidence of disease activity. We obtained data from, 79 patients (73 CD and, 6 with ulcerative colitis (UC)). Levels of fecal calprotectin before and after starting ustekinumab IV was available for, 44 patients and trough levels of drug for, 48 patients. Results: Baseline characteristics of the included patients are shown in Table, 1. Complicated forms (B2-B3;, 60, 6%) predominated and perianal disease was present in, 35.4% of patients. Only, 3 patients were naïve to biological treatments, 41.8% had received at least one and, 54, 5% more than, 2. The mean follow-up after the first IV administration was, 13.22 months (IQR, 2–37 months). Last dose used before the start of ustekinumab IV was, 90 mg /, 6 weeks in, 31.6% and, 90 mg /, 4 weeks in, 68.4% of the patients. After, 12 weeks of the first IV dose, 43% of patients achieve clinical remission (HBI<5 or pMS, 2) and, 59.5% at the end of follow-up. Basal fecal calprotectin decreased significantly at month, 12 and at end of follow-up (612.6 mg/kg vs, 384.1 mg/kg vs, 222 mg/kg; p = 0.0002 and p=0, 0048 respectively) (Figure, 1). Drug levels at the beginning of IV administration were, 2.6 mcg/ml (IQR, 0.13-11-69) and a significant increase from baseline was observed (week, 12–16:, 9.09 mcg/ml and after, 1 year:, 10.7 mcg/ml; both p <0, 001). At the end of the follow-up, 81% of patients maintain the treatment (figure 2). Conclusion: Patients who lose response to the intensified dose of ustekinumab sc could benefit from intravenous administration as maintenance treatment. This strategy achieves clinical remission in, 60% of the patients and allows to maintain the treatment in, 80% of them for at least, 12 months.